PENGARUH INFLASI DAN PDB TERHADAP PENERIMAAN PPN DI INDONESIA TAHUN 1992-2022 - Widya Oktaviani; Lili Syafitri; Aris Munandar (Politeknik Bisnis Indonesia, 2024)
Value Added Tax (VAT) revenue is one of the significant sources of government income. VAT plays a crucial role in supporting the country’s financial sustainability and financing various development programs. It is a consumption tax levied on the value added at each stage of production and distribution of goods and services. The purpose of this research is to examine the impact of inflation and Gross Domestic Product (GDP) on VAT revenue in Indonesia from 1992 to 2022. The study was conducted in Indonesia using observation methods on the websites of the Central Statistics Agency and Bank Indonesia, along with literature review and documentation. A saturated sample was used, covering 31 years of time series data. The data were analyzed using SPSS version 26, including classical assumption tests, multiple linear regression, and hypothesis testing. The partial results indicate that inflation has a negative and insignificant effect on VAT revenue. However, on the other hand, GDP significantly influences VAT revenue. This is due to increased productivity of goods and services in the economy, as well as an increase in the number of taxable objects (goods and services subject to taxation), leading to higher VAT revenue. Simultaneously, both inflation and GDP have a significant impact on VAT revenue.